Research on Problems with the Suspended Curtain Wall Structure of Xi'an Silk Road International Conference Center. Issue 1 (2nd January 2022) - Zhang, Zheng; Ding, Jiemin; Zhang, Yueqiang; Hao, Zhipeng
Abstract: This technical report mainly concerns the suspended curtain wall of Xi'an Silk Road International Conference Center. The upper part is suspended at the end of a 35.6 m cantilever truss, and the lower part is linked to a lower crescent shaped structure suspended by circular columns. According to the architectural requirements for the design of curtain walls, the stability of the curtain wall suspenders is studied first. The deformation of the curtain wall structure is analysed in depth to meet the design requirements for curtain wall systems. The overall cooperative analysis of the curtain wall structure and the main structure is carried out considering the influence of the main structure rigidity on the suspended curtain wall structure. Targeting various problems, the corresponding solutions and effective control measures are put forward from the viewpoint of design and construction. The results show that the ladder-shape composite column scheme has good lateral stability, which is suitable for a large-span suspended curtain wall system. The adverse deformation of the whole curtain wall can be effectively controlled by setting transverse members and improving the torsional rigidity of the corners. The design force and the forming state of hanging curtain wall structure can be ensured through construction measures such as pre-arching and the initial tension state.